144k views
1 vote
Simplify 9s-5s+2s-s for my work

2 Answers

1 vote

Lets say that 's' stands for 'sandwich'. It could be any noun you want that starts with the letter 's'.

9s represents having 9 sandwiches

5s means you have 5 sandwiches

and so on

Saying 9s-5s means you start with 9 sandwiches and take away 5 of them. So, 9s - 5s = (9-5)s = 4s. We're left with 4 sandwiches.

Then add on 2 more

9s - 5s + 2s = 4s + 2s = (4+2)s = 6s

We now have 6 sandwiches

Finally, take away 1 sandwich. The last "-s" in your given expression is the same as "-1s"

So,

9s - 5s + 2s - s = 9s - 5s + 2s - 1s

9s - 5s + 2s - s = 6s - 1s

9s - 5s + 2s - s = (6 - 1)s

9s - 5s + 2s - s = 5s

or you could write your work like this

9s - 5s + 2s - s = 9s - 5s + 2s - 1s

9s - 5s + 2s - s = (9 - 5 + 2 - 1)s

9s - 5s + 2s - s = 5s

Either way, the given expression simplifies to 5s. In the end, we have 5 sandwiches.

User Matt Williamson
by
4.7k points
2 votes

The answer is 5s, Hope this helps for your work.

User ReeganLourduraj
by
4.6k points